PAI TEACHER DESIGN TO DEVELOP MULTICUTURALISM EDUCATION AT MADRASAH ALIYAH - Imro Atun Sakurina; Khuriyah Khuriyah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2023)
this research is aimed describe how PAI teacher design in developing educational multiculturalism at MAN 1 Karanganyar. This research used descriptive qualitative approach and PAI teacher of the school as informants. In collecting data, the researcher used observation, documentation, and interview. The research results are the teachers have an understanding of diversity, multiculturalism, and hold on to human principles and values to develop educational multiculturalism. When the teaching and learning process the teachers mostly has used various approaches, strategies, and methods in accordance students’ characteristic that is implementing Negotiated Blended Learning. The teachers also avoided discriminatory effect by asking class administrator such as chairman and vice, also male and female students as gender representative. PAI teachers considered that the students as individual, who are from different backgrounds and characteristics, so that the teachers are able to foster awareness of mutual tolerance, respect each other. It was done by selecting learning model which cause to emerge cooperation and harmony that is cooperative learning. In creating equity for students, the teachers rolled students’ seats, and all students male and female were given equal opportunity to ask, and express their opinion. The next, the teachers has integrated learning materials with tribes, races, religions, cultures, ethnicities, and customs diversity in Indonesia.